2019
DOI: 10.18325/jkmr.2019.29.2.149
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Korean Traditional Medicine for Cervical Spondylotic Myelopathy

Abstract: Objectives This study was performed to research the trends of Korean traditional medicine treatment for cervical spondylotic myelopathy (CSM). Methods Clinical studies about Korean traditional medicine of CSM were searched in 7 online databases. We extracted the characteristics of selected studies according to author, publication year, country, research design, treatment methods, evaluation tools, and adverse events. Results Nineteen studies were selected in online databases. The included studies consist of 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Conservative treatment of CSM and cervical myelopathy include drug therapy, injection therapy, and physical therapy, among others [3]. Korean medicine treatment includes herbal medicine, acupuncture, moxibustion, pharmacopuncture, traction, and acupotomy [7]. Of which, acupotomy has been studied since 2006, with studies reported in 2007, 2014, 2017, and 2018 [5,7].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Conservative treatment of CSM and cervical myelopathy include drug therapy, injection therapy, and physical therapy, among others [3]. Korean medicine treatment includes herbal medicine, acupuncture, moxibustion, pharmacopuncture, traction, and acupotomy [7]. Of which, acupotomy has been studied since 2006, with studies reported in 2007, 2014, 2017, and 2018 [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…Korean medicine treatment includes herbal medicine, acupuncture, moxibustion, pharmacopuncture, traction, and acupotomy [7]. Of which, acupotomy has been studied since 2006, with studies reported in 2007, 2014, 2017, and 2018 [5,7]. Of these 5 studies, 4 were conducted in China and 1 was conducted in Korea where only 1 case was reported [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations